An Exploratory Study of Universal Design for Teaching Chemistry to Students With and Without Disabilities. (May 2015) - King-Sears, Margaret E.; Johnson, Todd M.; Berkeley, Sheri; Weiss, Margaret P.; Peters-Burton, Erin E.; Evmenova, Anya S.; Menditto, Anna; Hursh, Jennifer C.
In this exploratory study, students in four co-taught high school chemistry classes were randomly assigned to a Universal Design for Learning (UDL) treatment or a comparison condition. Each co-teaching team taught one comparison and treatment class. UDL principles were operationalized for treatment: (a) a self-management strategy (using a mnemonic, IDEAS) for the multi-step mole conversion process; (b) multi-media lessons with narration, visuals, and animations; (c) procedural facilitators with IDEAS for conversion support; and (d) student workbooks mirroring video content and containing scaffolded practice problems. All students completed a pre-test, post-test, and a 4-week delayed post-test. There were no significant differences between conditions; however, there was an interaction effect between students with and without disabilities for post-tests. Social validity indicated students found IDEAS helpful. Implications for future research include continued focus on disaggregated learning outcomes for students with and without disabilities for UDL interventions, and refinements for UDL interventions that benefit students with and without disabilities.